2017
DOI: 10.2196/mental.8311
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet and Mobile Phones for Self-Management of Severe Mental Health Problems: Qualitative Study of Staff Views

Abstract: BackgroundResearchers are currently investigating the feasibility, acceptability, and efficacy of digital health interventions for people who experience severe mental health problems such as psychosis and bipolar disorder. Although the acceptability of digital health interventions for severe mental health problems appears to be relatively high and some people report successfully using the Internet and mobile phones to manage their mental health, the attitudes of mental health care staff toward such approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 48 publications
9
91
0
1
Order By: Relevance
“…Participants believed that entering data on a DHI in the absence of any clinician involvement may be meaningless. Therefore, participants were willing to grant the care team access to their data, but had mixed views about whether this access should be automatic or user-initiated.Traditionally, symptom monitoring approaches tend to involve the automatic transfer of symptom information [48]; however, these findings suggest service users should have control over information transfer, which echoes views expressed by staff [49] and individuals with bipolar disorder [50] and first episode psychosis [51]. Concerns over third party access were also expressed and may be a barrier to DHI uptake by people with severe mental health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants believed that entering data on a DHI in the absence of any clinician involvement may be meaningless. Therefore, participants were willing to grant the care team access to their data, but had mixed views about whether this access should be automatic or user-initiated.Traditionally, symptom monitoring approaches tend to involve the automatic transfer of symptom information [48]; however, these findings suggest service users should have control over information transfer, which echoes views expressed by staff [49] and individuals with bipolar disorder [50] and first episode psychosis [51]. Concerns over third party access were also expressed and may be a barrier to DHI uptake by people with severe mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants were positive about the provision of DHIs to enhance user choice, provide an adjunct to existing options and reduce the number of face-to-face appointments required. A recent analysis of user reviews of apps for bipolar disorder highlighted that users had reported using these apps in conjunction with face-to-face care [52], whilst qualitative studies with staff and people experiencing severe mental health problems stressed the need for continued support during DHI engagement [49,51,[53][54][55]. Therefore, DHIs are seen by service users as a method to enhance face-to-face care, rather than replace existing support.…”
Section: Discussionmentioning
confidence: 99%
“…Participants did not consider apps as a standalone replacement for traditional professional management but rather as a tool to support and enhance treatment, a viewpoint consistent with clinicians’ beliefs in a qualitative study regarding apps for severe mental health issues [ 38 ]. The value in professional mental health treatment was strongly recognized, but participants utilized apps to support activities that coincided with their treatment beliefs, often when accessibility barriers hindered traditional mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, social media can be a helpful coping mechanism to facilitate self‐expression and communication with others with similar experiences and to access motivational content . Clinicians have observed occasions where online communication has been beneficial for clients' with SMI through accessible peer support and ability for anonymous self‐expression . Individuals are amenable to the idea of receiving mental health support via social media websites and have suggested the inclusion of social media components, such as moderated discussion forums, in future interventions .…”
Section: Introductionmentioning
confidence: 99%